The Madagascar International Cooperative Biodiversity Group (ICBG): Using Natural Products Research to Build Science Capacity - Miller, James S.; Birkinshaw, Christopher; Callmander, Martin (Ethnobotany Research and Applications, 2005)
In 1993, the National Institutes of Health funded a programto support multi-institutional partnerships to conduct natural products drug discovery in a manner to support conservation and economic growth. To date, ten InternationalCooperative Biodiversity Groups (ICBG) have been supported. The activities of the Madagascar ICBG projectare reviewed, first providing an overview of goals of the program to conduct botanical inventory, conservation analysis, and to collect samples for bioassay in Madagascar’snorthern complex, then focusing on efforts to build capacity to conduct these activities within Madagascar. This paper introduces the results of a recently conducted ethnobotanical training program.